Causal relationship between coherent self-awareness and basic psychological needs with psychological well-being: considering the mediating role of mind-awareness in students. - Abedin, Tayebeh; Ghodsi, Parvaneh; Taghiloo, Sadegh; Davaei, Mehdi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: appropriate educational facilities, along with the active and motivated minds of learners, will lead to the progress of the country; Therefore, one of the important research priorities in this field is to identify and investigate the effective factors in the mental health of students, which are considered the main components of the educational system. Therefore, the present study was conducted with the aim of investigating the causal relationship between coherent self-awareness and basic psychological needs with psychological well-being with regard to the mediating role of mindfulness in middle school students of Tehran. Method: This descriptive correlational study was conducted on a sample of 352 people, who were selected by multi-stage cluster sampling method from among all secondary school students of the 2nd district of Tehran in the academic year of 2019-1400. Ghorbani et al.’s (2008), basic psychological needs of LaGuardia et al.’s (2000), Rief’s psychological well-being (1989) and Freiburg’s mindfulness (2006) questionnaires were implemented and the data were collected using descriptive statistics, Pearson correlation and structural equation modeling methods in P>0.01 significance level was analyzed by AMOS software and SPSS version 24. Results: The structural model of predicting psychological well-being based on basic psychological needs and self-knowledge, with the mediation of mindfulness in students, had an acceptable and favorable fit (P<0.01); Therefore, it can be concluded that the satisfaction of basic psychological needs and self-knowledge of coherence with the mediation of mindfulness explains psychological well-being in middle school students. Conclusion: Considering the positive and meaningful relationship of psychological well-being with basic psychological needs and coherent self-knowledge and confirming the mediating role of mindfulness in this process and the importance of psychological well-being in nurturing and improving the academic performance of students, paying attention to the level of mindfulness and satisfying the basic psychological needs of students in schools It is very important and it is recommended that schools organize programs in their work program to improve the level of self-awareness of students and to familiarize and apply more concepts such as mindfulness, and to plan educational environments in a way that can meet the basic needs of students.